Equivalentes terapéuticos - Parra A., Manuel; Martínez M., Luis (Revista Hospital Clínico Universidad de Chile, 2007)
The quality of life without a doubt some, has improved thanks to medicines. The World-Wide Organization of the Health (the WHO) has recognized that the Good Practices of Manufactura (BPM) are the element most important to assure the quality a medicine. The security of the quality implies nonsmaller costs. The technical requirements to evaluate and to check that the pharmaceutical products are given to the markets under superior criteria in the matter of security, effectiveness and quality are defined by the Pharmaceutical Industry de Investigation. It is necessary that regulatory controls to pharmaceutical products exist, but these must be carried out with fairness for original products and similar products. Decree 1876 (Regulation of National Medicine Control) in its article 42 excepts to similar pharmaceutical products of the presentation of antecedents relative to selective and toxicologics farmacologics studies inanimals, clinical studies and farmacocinetics studies. The national medicine policy must assure the availability and rational access all the population to effectiveness medicines and guaranteed quality, reasonable insurances and of cost. At the present time, the quality assurance of our medicines is pending as far as effectiveness, security and bioequivalence. The quality of the Chilean pharmaceutical product does not pass the scrutinies international